PROGRESSIVE RETINAL NONPERFUSION IN ISCHEMIC CENTRAL RETINAL VEIN OCCLUSION. Issue 1 (January 2015) - Wykoff, Charles C.; Brown, David M.; Croft, Daniel E.; Major, James C.; Wong, Tien P.
Abstract : Background: Serial wide-field fluorescein angiography was performed on eyes with preproliferative (ischemic) central retinal vein occlusion to evaluate retinal perfusion. Methods: Serial wide-field fluorescein angiography was performed on 12 preproliferative central retinal vein occlusion eyes in the 3-year Rubeosis Anti-VEGF (RAVE) trial using the Staurenghi lens (Ocular Staurenghi 230SLO Retina Lens) with a scanning laser ophthalmoscope (Heidelberg HRA Spectralis). "Disk area" was defined anatomically for each eye. Results: Mean total field of gradable retina was 290 disk areas (range, 178–452). All eyes demonstrated extensive areas of retinal nonperfusion; at baseline, mean area of retinal perfusion was 106 disk areas (range, 37–129), correlating with a mean of 46.5% perfused retinal area (range, 19.1–56.4%). The area of retinal nonperfusion increased in all eyes with a mean loss of approximately 8.1% of perfused retinal area per year (range, 4.3–12.4%), which corresponded to a mean 15-disk areas (range, 12–35) of retina evolving from perfused to nonperfused annually. The extent of baseline and final nonperfusion was not significantly different between eyes that developed neovascularization and eyes that did not. Conclusion: In this population of severe central retinal vein occlusion eyes, profound retinal nonperfusion was observed with wide-field fluorescein angiography at baseline and the extent of nonperfusion progressed while undergoing anti-vascular endothelial growth factor therapy. Abstract : Profound retinal nonperfusion with progression was observed with wide-field fluorescein angiography in eyes with severe central retinal vein occlusion while undergoing anti-vascular endothelial growth factor therapy.